Lietuvos TSR Mokslų Akademijos Centrinės bibliotekos bibliografinis ir leidybinis darbas 1946-1985 metais - Ivaškevičius, Adolfas (Knygotyra, 1988)
In the post-war period, alongside completing and cataloging, bibliographic service was organized in the Central Library of the Academy of Sciences of the Lithuanian SSR. The 11th conference of directors of the libraries of the Academy of Sciences of the USSR in 1950 decided that bibliographical reviews of publications issued by Academies of Sciences in every Union Republic should be published. Following this decision, the Central Library compiled the first bibliographical index covering the publications of the Academy of Sciences and its scientists during the period 1941-1954. In 1956, this bibliographical index was published. Since then, such indices have been published annually. The total number of books published up to this time is 26. At the beginning of the sixties and afterwards, much attention was paid to the publishing of retrospective bibliographical indices. Linguistic, historic, geologic, and materials from other sciences were included. Much attention was also given to publishing monographs on book science.